Policy on Refusal of Repatriation of Indonesian Citizens Former ISIS Members and Unseen Security Threats - Umul Fadilatul Ulla; Zaky Ismail (Universitas Widya Mataram, 2026)
The defeat of ISIS has left many Indonesian citizens who were once members of the radical group trapped in conflict zones. However, this study argues that refusing repatriation will not completely eliminate security risks, as deportation loopholes will directly force Indonesia to accept returning Indonesian citizens without going through strict procedures. This study will use a qualitative descriptive approach and case study analysis to examine in depth Indonesia's decision to refuse repatriation and the security loophole from the policy. The case studies of Rullie Zeke and Ulfa, Indonesian citizens affiliated with ISIS, are used as examples of the limitations of deportation in preventing cross border radicalization and terrorism. Deportation makes countries vulnerable because they have to accept highly risky individuals without being able to refuse them, which ultimately weakens their longterm risk mitigation capacity. There is a potential for new, unseen threats if the policy of refusing repatriation continues to be implemented without other adaptive policies. Keywords: Deportation; Repatriation Policy; National Security.